2001
DOI: 10.1002/1521-3765(20010716)7:14<3069::aid-chem3069>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Oligosaccharides Display Both Rigidity and High Flexibility in Water as Determined by13C NMR Relaxation and1H,1H NOE Spectroscopy: Evidence ofanti-φ andanti-ψ Torsions in the Same Glycosidic Linkage

Abstract: The trisaccharide beta-D-Glcp-(1-->2)-beta-D-Glcp-(1-->3)-alpha-D-Glcp-OMe has been investigated by molecular dynamics (MD) simulations and NMR experiments in water. 13C spin-lattice (T1) and spin-spin (T2) relaxation times, together with 1H,13C NOE data were measured at two magnetic field strengths (9.4 and 14.1 T) in a 277 K D2O solution. Relaxation data interpreted by means of the model-free formalism revealed a rigid (S2 approximately 0.9) oligosaccharide tumbling in solution. 1H,1H Cross-relaxation rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 86 publications
3
22
0
Order By: Relevance
“…The (1?6)-linked disaccharides are characterized by two significantly populated states (B and A for I; C and D for G; the population of the former one being in both cases about twice that of the latter one; A and C:x in gt; B and D:x in gg), along with two alternative states with marginal populations for G only. In the literature, 210,211 the most stable states are sometimes referred to as syn-/ and (Table 1). They were also selected to illustrate the main intramolecular H-bonds present in this state (Table 5; (except for I and G) syn-w conformations (for I and G: syn-/(gt) and syn-/(gg)), while the alternative (metastable) states with different values of / or w are referred to as anti-/ or anti-w, respectively.…”
Section: Conformational States: Definition and Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…The (1?6)-linked disaccharides are characterized by two significantly populated states (B and A for I; C and D for G; the population of the former one being in both cases about twice that of the latter one; A and C:x in gt; B and D:x in gg), along with two alternative states with marginal populations for G only. In the literature, 210,211 the most stable states are sometimes referred to as syn-/ and (Table 1). They were also selected to illustrate the main intramolecular H-bonds present in this state (Table 5; (except for I and G) syn-w conformations (for I and G: syn-/(gt) and syn-/(gg)), while the alternative (metastable) states with different values of / or w are referred to as anti-/ or anti-w, respectively.…”
Section: Conformational States: Definition and Samplingmentioning
confidence: 99%
“…marginally populated (up to 1.3% at most) for the D-glucpyranose disaccharides in aqueous solution at 300 K and 1 bar. Experimentally, population estimates ranging from a fraction of a percent up to 92 13% have been proposed for these metastable states in disaccharide derivatives and trisaccharides (J-coupling 92,106 or/ and NOE-based 93,212,213 mixed NMR/MD approaches 210,211 ). Note that some of these estimates have subsequently been questioned.…”
Section: Comparison With Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In a related study of another trisaccharide the intraresidue distance also showed good agreement to simulations, but in this case the model-free approach resulted in a slightly shorter distance when NOE data were used and a somewhat longer distance when TROE data were employed. [42] Subsequently, when ISPA is used (vide infra), a reverse relationship for r NOE vs. r TROE is obtained for the short trans-glycosidic distances. Therefore, the experimental differences should represent the accuracy of the data.…”
Section: Resultsmentioning
confidence: 99%
“…59 However, it was instead highly flexible and further studies of the trisaccharide showed that both anti-φ and anti-ψ conformational states were populated as determined by NMR spectroscopy and interpreted using molecular dynamics (MD) simulations. 60 In conformational analysis of oligosaccharides 1 H, 1 H NOEs play an important role but the decimate the contribution from a third proton to the desired interaction is to chemically exchange 1 H for 2 H atoms, which effectively eliminates contributions via the undesired relaxation pathway. 63,64 Thus, if spectral appearance permits selective irradiation, it is the method of choice, otherwise a chemical substitution approach is needed.…”
Section: Primary Structure Determinationmentioning
confidence: 99%